Pengaruh Penerapan Kontrak Belajar (Learning Contracts) Terhadap Kedisiplinan Belajar Siswa Kelas X dan XI di Sekolah Menengah Kejuruan (SMK) Bakti Karya Parigi - Anwar Hidayat; Elis Agustin; Siti Aisah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
This study aims to determine the effect of implementing a learning contract on student learning discipline. The research method used is a simple linear regression method by performing the F test and t test. The research instrument used is a questionnaire, the population used is class X and XI students at SMK Bakti Karya Parigi with a total sample of 33 respondents (students). The data analysis used is descriptive data analysis technique. From the results of a simple linear regression test, it is knownthat the value of t count = 2.054 > t table 2.040 with a significance value of 0.049 < 0.05. Therefore Ho is rejected and Ha is accepted, thus there is an influence between the learning contract variable (X) on student learning discipline (Y). Based on the results and data analysis regarding the effect of implementing a learning contract (Learning Contract) on the learning discipline of class X and XI students at SMK Bakti Karya Parigi, it can be concluded that thereis an influence between the application of a learning contract (Learning Contract) on the learning discipline of class X and XI students at SMK Bakti Karya Parigi. The calculated r value of learning contracts and student learning discipline is 0.346 and the coefficient of determination or (R Square) is 0.120, which means that the effect of the learning contract variable on the student learning discipline variable is 12%, the rest is determined by other variables not discussed in this study.